1998
DOI: 10.1021/jf970866x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Postharvest Treatment with Putrescine and Calcium on Endogenous Polyamines, Firmness, and Abscisic Acid in Lemon (Citrus lemonL. Burm Cv. Verna)

Abstract: Fruit firmness, free polyamine levels (putrescine, spermidine, and spermine), abscisic acid (ABA), and color index were determined in lemon fruit at two ripening stages (at color break and fully yellow) after vacuum infiltration with 1mM putrescine and 1 mM calcium chloride. Both treatments significantly increased fruit firmness as compared with control fruit in stage 1 lemons. Putrescinetreated fruits showed higher levels of firmness and lower weight loss than calcium-treated or nontreated fruits during stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
13

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 34 publications
(51 reference statements)
6
52
0
13
Order By: Relevance
“…In another report, Put treatment resulted in reduced or slow color change, ethylene emission and respiration in kiwifruit 60 . Similarly, Put applied by vacuum infiltration notably increased lemon fruit firmness and delayed the color change as compared to the control 85 . As is known, fruit softening is primarily due to breakdown of the cell wall.…”
Section: Use Of Exogenous Polyamines In Postharvest Managementmentioning
confidence: 83%
See 1 more Smart Citation
“…In another report, Put treatment resulted in reduced or slow color change, ethylene emission and respiration in kiwifruit 60 . Similarly, Put applied by vacuum infiltration notably increased lemon fruit firmness and delayed the color change as compared to the control 85 . As is known, fruit softening is primarily due to breakdown of the cell wall.…”
Section: Use Of Exogenous Polyamines In Postharvest Managementmentioning
confidence: 83%
“…As is known, fruit softening is primarily due to breakdown of the cell wall. The above-mentioned effects of polyamines on fruit texture (fruit firmness and fruit softening) could be ascribed to their properties of inhibiting enzymes degrading pectic acids 49,85 and/or to their ability to bind to cell walls and membranes 61 , leading to rigidification of cell walls and stabilized membranes. Inhibited ethylene production might also account for the enhanced firmness and delayed softening.…”
Section: Use Of Exogenous Polyamines In Postharvest Managementmentioning
confidence: 99%
“…These results are in accordance with the finding of Champa et al (2014) on grapes who reported that Putrescine treatments effectively retarded the degradation of stem colour during storage period. Similarly, Valero et al (1998) and Martinez-Romero et al (2001) also reported that postharvest polyamine applications delayed colour changes in lemon and apricot during storage. …”
Section: Stem Browningmentioning
confidence: 79%
“…Postharvest application of Put, by immersion or vacuum infiltration, has been reported to delay fruit ripening and extend shelf life in some climacteric or nonclimacteric fruits such as lemon (Valero et al, 1998), apricot (Martinez-Romero et al, 2001), mango (Malik and Singh, 2005), strawberry (Khosroshahi et al, 2007), sweet cherry (Bal, 2012), plum (Serrano et al, 2003;Davarynejad et al, 2013) and peach (Bal, 2013). Champa et al (2014) reported that prestorage dip treatment of 0.5 mM Put or 0.5 mM Spd or 1.0 mM Spm for 5 min maintained the quality and extended the shelf life of grape cv.…”
Section: Introductionmentioning
confidence: 99%
“…El tratamiento retrasa el cambio de color y disimuye el contenido endógeno de ABA. Por otro lado, incrementa el nivel endógeno de Put y Spd en los frutos más maduros (Valero et al, 1998). Pero el papel hormonal de las PAs es controversial.…”
Section: Poliaminasunclassified